Parallel reductions in phenolic constituents resulting from the domestication of eggplant. (July 2015) - Meyer, Rachel S.; Whitaker, Bruce D.; Little, Damon P.; Wu, Shi-Biao; Kennelly, Edward J.; Long, Chun-Lin; Litt, Amy
Graphical abstract: The domestication process converged on lower phenolics in eggplant and related nightshade crops, shown by quantification and analysis of 32 compounds in 93 Solanum fruit. Highlights: Phenolic diversity was assessed in eggplants landraces and wild relatives. Domestication reduced health-beneficial hydroxycinnamic acid derivatives. Small Malesian eggplants, of separate origin, contain more polyamine conjugates. Genetic background is correlated with phenolic profiles but geographic origin is not. Selection on taste, size, and texture drove sometimes convergent changes in profiles. Abstract: Crop domestication is often accompanied by changes in metabolite compositions that alter traits such as flavor, color, or other beneficial properties. Fruits of eggplants ( Solanum melongena L.) and related species are abundant and diverse in pharmacologically interesting phenolic compounds, particularly hydroxycinnamic acid (HCA) conjugates such as the antioxidant caffeoylquinic acids (CQA) and HCA-polyamine amides (HCAA). To understand metabolite variability through the lens of natural and artificial selection, HPLC-DAD was used to generate phenolic profiles for 32 compounds in fruits from 93 accessions representing 9 Solanum species. Profiles were used for identification of species-level and infraspecific chemical patterns across both genetic distance and landscape. Sampling of plant lines included the undomesticated progenitor of eggplant and Asian landraces with a genetic background associated with three Asian regions near proposed separate centers of domestication to test whether chemical changes were convergent despite different origins. Results showed ten compounds were unique to species, and ten other compounds varied significantly in abundance among species. Five CQAs and three HCA-polyamine conjugates were more abundant in wild (undomesticated) versus domesticated eggplant, indicating that artificial selection may have led to reduced phenolic levels. No chemical abundance patterns were associated with site-origin. However, one genetically distinct lineage of geographically-restricted SE Asian eggplants ( S. melongena subsp. ovigerum ) had a higher HCAA content and diversity than other lineages, which is suggested to be related to artificial selection for small, firm fruit. Overall, patterns show that fruit size, palatability and texture were preferentially selected over health-beneficial phytochemical content during domestication of several nightshade crops.